Improving patient satisfaction in glaucoma care - Islam S (Dove Medical Press, 2017)
Samsul Islam, Ahmad Salha, Saeed Azizi Faculty of Medicine, St George’s Hospital Medical School, London, UKWe read the article by Foo et al1 with great interest. We were intrigued by the factors influencing satisfaction rates among glaucoma patients. It made us question what changes could be made in the future attempting to improve patient satisfaction. Similar to Foo et al,1 we were also surprised to find a lower end-point intraocular pressure was linked with increased patient dissatisfaction. As stated by Foo et al,1 other studies exploring clinical outcomes and patient satisfaction found that a positive clinical state was linked to higher patient satisfaction. Prakash2 proposes a three-way association between patient satisfaction, increased compliance, and better clinical outcomes. Hence, in attempting to investigate patient satisfaction, it would be appropriate to assess patient compliance and clinical outcomes.View the original paper by Foo and colleagues.